2014
DOI: 10.1016/j.foreco.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Factors explaining variability in woody above-ground biomass accumulation in restored tropical forest

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Secondary forests comprise an increasing area of the tropics and play an important role in global carbon cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 76 publications
(121 reference statements)
5
78
1
Order By: Relevance
“…Plantation of trees on former agriculture lands substantially increases biomass accumulation during the first few years of forest recovery in the restored tropical forest in Costa Rica [74]. In addition to the small and fragmented indigenous forest patches, the Taita Hills host plantations of exotic tree species, such as Cupressus lusitanica, Eucalyptus spp., Grevillea robusta and Pinus spp.…”
Section: Determinants Of Aboveground Biomass Distributionmentioning
confidence: 99%
“…Plantation of trees on former agriculture lands substantially increases biomass accumulation during the first few years of forest recovery in the restored tropical forest in Costa Rica [74]. In addition to the small and fragmented indigenous forest patches, the Taita Hills host plantations of exotic tree species, such as Cupressus lusitanica, Eucalyptus spp., Grevillea robusta and Pinus spp.…”
Section: Determinants Of Aboveground Biomass Distributionmentioning
confidence: 99%
“…aboveground biomass accumulation relative to natural succession (Lugo, 1992;Aide et al, 1995;Cusack and Montagnini, 2004;Holl and Zahawi, 2014), particularly since plantation species are often selected for rapid growth. Biomass accumulation in naturally regenerated secondary forests, especially those regrowing on abandoned agricultural land, tends to occur in later successional stages (Brown and Lugo, 1990;Guariguata and Ostertag, 2001;Holm et al, 2012), though rates depend on the intensity of previous land-use activities (Holl and Zahawi, 2014;Silver et al, 2000).…”
Section: No Structural Effects Of Land-use History In Similarly Aged mentioning
confidence: 99%
“…Applying this rate to the La Calandria data would suggest a forest age of only 30 years, which is inconsistent with the trunk diameters, as noted above [24]. However, various studies have noted that rates of biomass accumulation during reforestation can vary greatly depending on numerous factors, many related to previous land-use [25]. For example, a study by Uhl et al [26] found that carbon accumulation rates on reforested pasture varied by more than an order of magnitude depending on the duration and intensity of grazing.…”
Section: Above-ground Biomassmentioning
confidence: 89%
“…Both accumulation rates we measured in the secondary forests are much lower than those observed in previous studies of carbon accumulation in tropical secondary forests, for example, the aforementioned rate of 4.9 tC ha −1 yr −1 measured in Peruvian cloud forests [23], a rate of 5.5 tC ha −1 measured in the Amazonian Basin [27], or the hypothetical rate suggested above for the MVI mature forest of 2.75 tC ha −1 . We speculate, therefore, that reforestation on these plots is limited by some factor, such as nutrient availability, resulting from prior landuse [25], or nutrient limitation of the rhyolitic material.…”
Section: Above-ground Biomassmentioning
confidence: 99%